The association of vegetable consumption and physical activity with chronic obstructive pulmonary disease among community-dwelling adults aged 40 years or above in China - Kang, Jian; Deng, Xiaojing; Wang, Wenjun; Cheng, Hui; Hong, Yalin; Xu, Huiqing; Xu, Yunting; Ao, Guofeng; Xu, Jian; Bian, Yeping; Ye, Qing (Frontiers in Nutrition, 2025)
AimsThis study aimed to examine the associations of vegetable consumption and physical activity (PA) with chronic obstructive pulmonary disease (COPD) among community-dwelling adults in regional China.MethodsEligible participants were community-dwelling adults aged 40 years or above and were randomly selected from Nanjing municipality of China in 2023. Spirometry-based newly-identified COPD was treated as the outcome event, which was defined as post-bronchodilator FEV1/FVC < 0.70 and without other lung function impaired diseases, and not previously diagnosed as COPD. Independent variables were vegetable intake and PA. Logistic regression models were employed to compute odds ratio (OR) and 95% confidence interval (CI) for investigating associations of vegetable consumption and PA with COPD.ResultsAmong the 5,567 participants analyzed, the prevalence of spirometry-based newly-identified COPD was 14.8% (95% CI = 13.9%, 15.8%). After adjustment for socio-demographic characteristics and other potential confounding factors, participants who met vegetable consumption criteria were less likely to experience COPD compared to those who did not meet vegetable intake recommendation (OR = 0.84; 95%CI = 0.71, 0.98), while participants with sufficient PA were also less likely to experience COPD compared to physically inactive subjects (OR = 0.79; 95%CI = 0.67, 0.94). Additionally, participant who met vegetable consumption recommendation and engaged in sufficient PA were also at much lower odds to experience COPD compared to those who did not meet vegetable intake recommendation and were physically inactive (OR = 0.67; 95%CI = 0.53, 0.85).ConclusionsVegetable consumption and PA were individually and jointly associated with CODP among community-dwelling adults in regional China. This study highlighted that, from public health perspective, intervention of vegetable consumption and PA may be of help for reducing the odds of experiencing COPD.